From the eye of the albatrosses: a bird-borne camera shows an association between albatrosses and a killer whale in the Southern Ocean. - Kentaro Q Sakamoto (Public Library of Science (PLoS), 2009)
Albatrosses fly many hundreds of kilometers across the open ocean to find and feed upon their prey. Despite the growing number of studies concerning their foraging behaviour, relatively little is known about how albatrosses actually locate their prey. Here, we present our results from the first deployments of a combined animal-borne camera and depth data logger on free-ranging black-browed albatrosses (Thalassarche melanophrys). The still images recorded from these cameras showed that some albatrosses actively followed a killer whale (Orcinus orca), possibly to feed on food scraps left by this diving predator. The camera images together with the depth profiles showed that the birds dived only occasionally, but that they actively dived when other birds or the killer whale were present. This association with diving predators or other birds may partially explain how albatrosses find their prey more efficiently in the apparently 'featureless' ocean, with a minimal requirement for energetically costly diving or landing activities.